Dampak kecanduan gadget pada perilaku anak-anak sekolah dasar: studi kualitatif - Luthfi Hidayat; Nandang Budiman (Journal of Educational and Learning Studies, 2025)
This study aims to investigate the impact of exposure to negative content on gadgets on elementary school children's behavior. Through interviews and observations, data were obtained from two elementary schools with participants from grades 5 and 6. The results showed that exposure to bad content, harsh words, and pornography on gadgets contributed to the emergence of aggressive behavior, impolite behavior, lack of social interaction, change in mindset, and negligence in worship in elementary school children. Factors such as the degree of accessibility of negative content, duration of exposure, age of child and environmental influences play a significant role in the observed impact. In this context, the roles of parents, schools and government are crucial in protecting children from exposure to negative content. Active supervision, education about safe content, use of access restriction devices, and development of media literacy skills in elementary school children are effective protection strategies. Public awareness about the importance of supervising and managing the use of gadgets in elementary school children also needs to be increased. This research provides an in-depth understanding of the impact of exposure to negative content on gadgets on elementary school children's behavior and emphasizes the need for child protection in the digital era.